Analysis of the Difference between Hydraulic Fracturing and Flow Channel Fracturing - Mia Ferian Helmi; Muhammad Zakiy Y.; Dinar Kaesti; Maulida Aulia Fadhina; Anisa Novia Risky (Journal of Petroleum and Geothermal Technology, 2020)
As time goes by, there will be a decline in formation productivity, as reflected in the decline in the rate of oil production from production wells. The decline in the rate of production was caused by many things such as a decrease in reservoir pressure, also formation damage. Where damage to the formation will result in a decrease in rock permeability. The decrease in rock permeability is caused by the blockage of rock pores due to the invasion of solids and drill mud filtrate, cementing, fluid fluids or previous stimulation. Besides the small rate of oil production can also be caused by the low natural permeability of rocks. With the decreasing productivity of the formation, it is necessary to make efforts to increase the productivity of the formation again, where one of them is by the method of hydraulic fracture stimulation. In this analysis, we will discuss the difference between conventional stimulation methods and flow channel fracturing. Flow channel fracturing is a fracturing process by making a network around proppant granules to form proppant pillar, so that a path is formed for the fluid to flow more easily. What distinguishes between conventional hydraulic fracturing with flow channel fracturing is the resulting fracture form, fracturing fluid injection pattern, and the amount of proppant used.